Handbook on public policy and food security - Hendriks, Sheryl L.; Babu, Suresh Chandra (Edward Elgar Publishing, 2024)
The Handbook on Public Policy and Food Security provides multi-disciplinary insight into food security analysis across the seventeen Sustainable Development Goals (SDGs). As food security is an essential outcome and a part of sustainable and healthy food systems, this Handbook addresses the urgent need to provide a comprehensive overview of the field’s current developments.